A general approach for the direct fabrication of metal oxide-based electrocatalysts for efficient bifunctional oxygen electrodes. Issue 4 (23rd March 2017) - Wang, Jie; Wu, Zexing; Han, Lili; Xuan, Cuijuan; Zhu, Jing; Xiao, Weiping; Wu, Jianzhong; Xin, Huolin L.; Wang, Deli
Abstract : Nitrogen doped carbon supported Ni@NiO, MnO and Co@CoO catalysts have been successfully prepared via a simple one-pot synthetic method. As air catalysts in aqueous rechargeable Zn–air batteries, Co@CoO/NDC-700 exhibits much better bifunctional catalytic and battery performance. Abstract : A simple one-pot synthetic strategy for the general preparation of nitrogen doped carbon supported metal/metal oxides (Co@CoO/NDC, Ni@NiO/NDC and MnO/NDC) derived from the complexing function of (ethylenediamine)tetraacetic acid (EDTA) is developed. EDTA serves not only as a resource to tune the morphology in terms of the complexation constant for M–EDTA, but also as a nitrogen and oxygen source for nitrogen doping and metal oxide formation, respectively. When the materials are used as electrocatalysts for the oxygen electrode reaction, Co@CoO/NDC-700 and MnO/NDC-700 show superior electrocatalytic activity towards the oxygen reduction reaction (ORR), while Co@CoO/NDC-700 and Ni@NiO/NDC-700 exhibit excellent oxygen evolution reaction (OER) activities. Taken together, the resultant Co@CoO/NDC-700 exhibits the best catalytic activity with favorable reaction kinetics and durability as a bi-functional catalyst for the ORR and OER, which is much better than the other two catalysts, Pt/C and Ir/C. Moreover, as an air electrode for a homemade zinc–air battery, Co@CoO/NDC-700 shows superior cell performance with a highest power density of 192.1 mW cm −2, the lowest charge–discharge overpotential and high charge–discharge durability over 100 h.